2008
DOI: 10.1128/jvi.02509-07
|View full text |Cite
|
Sign up to set email alerts
|

E Protein Domain III Determinants of Yellow Fever Virus 17D Vaccine Strain Enhance Binding to Glycosaminoglycans, Impede Virus Spread, and Attenuate Virulence

Abstract: The yellow fever virus (YFV) 17D strain is one of the most effective live vaccines for human use, but the in vivo mechanisms for virulence attenuation of the vaccine and the corresponding molecular determinants remain elusive. The vaccine differs phenotypically from wild-type YFV by the loss of viscerotropism, despite replicative fitness in cell culture, and genetically by 20 amino acid changes predominantly located in the envelope (E) protein. We show that three residues in E protein domain III inhibit spread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
99
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 39 publications
6
99
0
Order By: Relevance
“…Attenuation of YFV-17D has been attributed to mutations in the YFV-17D envelope protein, which may hinder spread of the virus to visceral tissues, and was recently linked to reduced quasispecies diversity (Beck et al, 2014;Hahn et al, 1987;Lee & Lobigs, 2008). Considering that YFV-17D is currently being used in chimeric vaccines to JEV, and for the development of vaccines to WNV and DENV, a better understanding of its attenuation is imperative (Guirakhoo et al, 2006;Guy et al, 2010;Monath et al, , 2006Pugachev et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Attenuation of YFV-17D has been attributed to mutations in the YFV-17D envelope protein, which may hinder spread of the virus to visceral tissues, and was recently linked to reduced quasispecies diversity (Beck et al, 2014;Hahn et al, 1987;Lee & Lobigs, 2008). Considering that YFV-17D is currently being used in chimeric vaccines to JEV, and for the development of vaccines to WNV and DENV, a better understanding of its attenuation is imperative (Guirakhoo et al, 2006;Guy et al, 2010;Monath et al, , 2006Pugachev et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…YFV can cause a viscerotropic disease resembling human disease, but only in peripherally injected immunodeficient animals such as mice deficient for IFN-a/b receptors (Meier et al, 2009). Peripheral injection of YFV-17D in adult mice lacking both IFN-a/b receptors and IFN-c receptors can cause a lethal neurotropic infection with transient viral infection of visceral organs and no observed tissue damage (Meier et al, 2009;Lee & Lobigs, 2008;Thibodeaux et al, 2012). Using a genetically marked pool of viruses, we previously found that YFV-17D encounters no major barriers that restrict viral diversity or dissemination in mice that lack IFN-a/b receptors (Erickson & Pfeiffer, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…route. Previous studies with engineered or selected mutants of WNV and some other JEV complex flaviviruses have identified single amino acid mutations that can attenuate mouse neuroinvasiveness (13,15,16,74,75) by multiple mechanisms that may be associated with direct or indirect effects on receptor binding or with increased glycosaminoglycan binding due to charge changes. Although it is possible that the reductions in the virulence of the EIII chimeras may have occurred due to negative effects on virion assembly, structure, or stability, the lack of obvious effects on in vitro behavior suggests that specific characteristics of the particular EIII sequence used likely play a more significant role in determining viral pathogenesis in mice.…”
Section: Discussionmentioning
confidence: 99%
“…The NS1 protein was preceded by its authentic signal peptide and the NS2A protein was C-terminally fused to an influenza virus hemagglutinin (HA) epitope tag (Pro-TyrAsp-Val-Pro-Asp-Tyr-Ala-Gly), which allows recovery of NS2A by immunoprecipitation with monoclonal antibody (mAb), 12CA5 (Wilson et al, 1984). To introduce amino acid substitutions in the octapeptide region, a fusion polymerase chain reaction (PCR) approach was employed (Lee and Lobigs, 2008) using the upstream primer, 5'-ACTGGATTGAGAGTGGACTCAATG-3', and downstream primer, 5'-CTGATCAGCGAGCTCTAGCATTTAAGGTGA-3', in combination with the corresponding mutagenesis primers (sequences will be provided upon request). Construction of mutant derivatives from plasmid, pRc/CMV.NS1-2A.HA, was by double digestion of mutagenized fragments (932 bp) and the corresponding ns1-ns2A gene region in the wild-type (wt) plasmid with restriction enzymes, PpuMI and XbaI, and replacement of the wt with a mutated cDNA fragment.…”
Section: Eukaryotic Expression Plasmidsmentioning
confidence: 99%